Immunogenicity and safety of measles-mumps-rubella and varicella vaccines coadministered with a fourth dose of Haemophilus influenzae type b and Neisseria meningitidis serogroups C and Y-tetanus toxoid conjugate vaccine in toddlers<subtitle>A pooled analysis of randomized trials</subtitle> - Kristina A. Bryant; Jodie McVernon; Colin D. Marchant; Terry Nolan; Gary S. Marshall; Peter Richmond; Helen Marshall; Michael Nissen; Stephen B. Lambert; Emmanuel Aris; Narcisa Mesaros; Jacqueline M. Miller (Taylor & Francis Group, 2012)
A pooled analysis was conducted of 1257 toddlers who received a fourth dose of Haemophilus influenzae type b-Neisseria meningitidis serogroups C and Y-tetanus toxoid conjugate vaccine (HibMenCY-TT) or Hib conjugate vaccine (Hib polysaccharide conjugated to N. meningitidis outer membrane protein) coadministered with measles-mumps-rubella (MMR) and varicella (VAR) vaccines (NCT00134719/NCT00289783). Noninferiority of immunological responses to MMR and VAR was demonstrated between groups and incidences of MMR- and VAR-specific solicited symptoms were similar, indicating that HibMenCY-TT can be coadministered with MMR and VAR.